Allergic Proctocolitis (AP) with Protein Losing Enteropathy (PLE): A Case Report - Akter, Sharmin; Sabiha, Aysha; Subha, Nahide E; Sayeed, Maimuna; Dey, Bishnu Pada; Karim, ASM Bazlul (Dhaka Shishu (Children) Hospital Journal, 2022)
Abstract not available DS (Child) H J 2021; 37(1): 75-77